Acute Necrotizing Pancreatitis in the Setting of CMV Viremia and AIDS: A Case Report and Review of Literature from 1980 to 2012 - Osiro, Stephen; Muhammad, Raza; Ruiz, Jose; Sladen, Anatole; Mathenge, Njambi; Tiwari, Kevin J (JOP. Journal of the Pancreas, 2012)
Context Cytomegalovirus (CMV)-induced pancreatitis in patients with AIDS is a known entity with poor prognosis. Case report We report a case of a 43-year-old woman with AIDS and CMV viremia who was evaluated for hypotension and found to have severe necrotizing pancreatitis. The authors have also conducted a MEDLINE search for CMV-induced pancreatitis from 1980 to 2012 and reviewed the pertinent results. Discussion Until mid-1990s in the United States, pancreatitis due to CMV was mainly diagnosed at autopsy in AIDS patients. However, presumably due to the advent of antiretroviral therapy, there has since been a significant decline in the number of reported cases among these individuals. Rather, our review revealed that the occurrence of CMV-induced pancreatitis has since been described in a variety of clinical settings, ranging from patients on corticosteroid therapy to immunocompetent persons. Conclusions Clinicians need a high index of suspicion to timely diagnose CMV-induced pancreatitis as patients often present with non-specific signs and symptoms. As it occurred in our case, early intervention is crucial and may alter the outcome in such patients. Image: Immunohistochemistry study showing human herpes virus type 8 (HHV-8).